Sustainable development: A Malaysian perspective - Abdulrazak, S.R.; Ahmad, Fauziah Sh. (Elsevier Ltd., 2014)
Sustainable development is all the rage. Malaysian firms too have been quick to jump into the bandwagon, especially with regards to their corporate social responsibility (CSR) initiatives. However, sustainable development has been increasingly interpreted from a strictly Western-centric value system.This may pose challenges to Malaysian firms as they adopt sustainable practices into their operations.Four key issues are presented and discussed, particularly in relation to Malaysian’s socioeconomic landscape.Following that, this paper calls for a return to the fundamentals of sustainable development, which is unfettered to value suppositions and instead focused on more pragmatic reasons.To that end, this paper proceeds to make recommendations of a more suitable approach in embracing sustainable development in Malaysia that would bring about a virtuous cycle of enrichment for the business sector as well as the society.